The Local Supporting Approaches Scaling up the Capacity of Reconstruction in Nepal : Local and Social support in Reconstruction - Chongbang, Nirmal (International Journal of Entrepreneurship and Business Management, 2022)
Disaster reflects a multi-fold impact on vulnerable communities such as children, women, and people living with disabilities. The study identifies the multiplier impact of hazard induce disasters, Covid019 pandemic, and regular strikes into poor and marginalized communities. Tried to be unmasking the effectiveness of local support initiatives as social recovery support from the neighbor, communities, non-state actors, and the state. The paper brings out how the social support, and protection practices can scale up its cost in disaster recovery initiates in disaster-affected communities in Gandaki province, Nepal. An online (google) based survey form was developed, and distributed to potential frontline workers, NGO staff, INGO staff, and UN staff based on their project area. Respondents were randomly divided into two groups (local support, and external support) and asked for their supporting practices while the disaster has occurred at the local level, and responses were analyzed at the explanatory level through the regression. While testing the hypothesis that local social support leads to higher resilience capacity in the disaster-affected household with compare to external support, which results showed that local level support was better with comparing of external support during disaster response and recovery. Study results suggested that household, neighbor, and local community support was quick, applicable, and easier to adopt than a comparison of external supporters. Based on the study, further development intervention should be centered on the capacity to strengthen local households, neighborhoods, community-based organizations, and local states rather than expecting external support. The study paper explores the local supporting practices on reconstruction and recovery, which is the novelty approaches in local supporting engagement on speedy recovery initiatives in Nepal.